Pengaruh Pengalaman Kerja Audit, Tekanan Waktu dalam Penyelesaian Audit terhadap Kinerja Audit Internal - Delfiana Jesika; Maria Gai; Aldensia Bernoli; Josua Buke; Elisabet Suna; Susana Purnamasari Baso (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Internal auditing plays a crucial role in supporting transparency, accountability, and effective corporate governance within organizations. However, the performance of internal auditors is often influenced by individual and situational factors, particularly work experience and time pressure during audit completion. Limited experience may reduce auditors’ ability to identify risks accurately, while excessive time pressure can lead to rushed procedures and decreased audit quality. This study aims to examine the influence of auditor work experience and time pressure on internal audit performance. The research employs a qualitative approach using a library research method by reviewing and analyzing relevant literature from academic journals, books, and previous empirical studies related to internal auditing. The analysis indicates that auditor work experience has a positive effect on internal audit performance, as experienced auditors demonstrate higher technical competence, better judgment, and more effective audit execution. In contrast, time pressure has a negative impact on audit performance because it increases the likelihood of procedural omissions and judgment errors. These findings suggest that improving auditor experience and managing audit time allocation are essential to maintaining high-quality internal audit performance.